Optimal robust monetary policy in a small open economy - Marine Charlotte André; Sebastián Medina Espidio (Banco de México, 2022)
We study an optimal robust monetary policy for a small open economy. The robust control approach assumes that economic agents cannot assign probabilities to a set of plausible models and rather focuses on the worst possible misspecification from a benchmark model. Our findings suggest that, first, conducting a global robust optimal monetary policy is limited as deviations from the benchmark model lead to multiple equilibria. Second, when the central bank considers uncertainty only in the IS Curve or in the UIP, the space of unique solutions is expanded. In fact, the central bank reacts more aggressively to demand and real exchange rate shocks when it is robust to misspecifications in the IS curve only. Finally, our results suggest that the global robust optimal monetary policy is limited due to inflation persistency and the low exchange rate pass-through. The importance of anchoring inflation expectations is highlighted.
Keywords: C62; D83; D84; E52; E58; 330; Robust control; model uncertainty; optimal monetary policy; small open economy